Preparation Of Digital Marketing Strategies In The Abakura Matic Business - Houce mariano; Golan Hasan (Universitas Internasional Batam, 2023)
Digital marketing is one of the marketing strategies using the internet and information technology to expand traditional marketing functions. Digital marketing can help marketers establish relationships with customers to increase customer loyalty. The use of digital marketing is widely practiced by several companies. In addition to digital marketing, another factor that can affect customer loyalty is customer satisfaction. Because to retain old customers, marketers can increase satisfaction. If the customer is satisfied, then he will show repurchase behavior and encourage loyalty. this research aims to develop a marketing strategy so that the business being run now is increasing and is also increasingly recognized by the wider community through digital marketing that will be applied. for example, such as being more active on Instagram social media by creating interesting photo or video content and can capture the attention of the wider community.